Factors Affecting Efl Learners in Learning English Pronunciation - Abdul Rosyid (Pedagogia: Jurnal Ilmiah Pendidikan, 2016)
The purpose of this research is to investigate some factors hindering Sundanesse in learning English pronunciation. This research attempts to answer the following research questions: What are the factors affecting Sundanesse in learning English pronunciation? The participants of this study are 30 students who are still in the second semester in English Education Study Program, Pakuan University. The data were collected through documentation in a form of audio recording, and in-depth interview with six representative participants. The major findings of this study are: There are three major factors affecting Sundanesse in learning English pronunciation, among others are; Mother tongue influence, Age and Target language exposure (2) The difficulties faced by Sundanesse in learning English pronunciation are mostly in terms of segmental features; such as vowels, consonants and diphthong, and supra-segmental features like intonation, stress and linking sound.